Health-Related Quality of Life in a Sample of Chronic Obstructive Pulmonary Disease Patients in AL-Diwanyia Province /Iraq. - Akram H Kareem; Dheyaa J. Kadhim (College of Pharmacy University of Baghdad, 2020)
The effect of mental and physical health on the feelings of subject welfare is known as health-related quality of life. The chronic obstructive pulmonary disease is a common respiratory diseases. Assessment of health-related quality of life is considered important in such chronic disease. The objective of the current study was to measure health-related quality of life in a sample of chronic obstructive pulmonary  patients in AL- Diwanyia city/Iraq. This study was carried out on 150 already diagnosed COPD patients who attended to the Center of Respiratory Diseases/AL-Diwaniyah Teaching Hospital during September  2019 to January 2020. The Arabic version of St George's Respiratory Questionnaire was used to assess the health-related quality of life. The mean symptoms score was 48.65 ±7.17, the mean activity score was 62.39 ±5.81, the mean impact score was 42.83 ±7.90 and the total score 49.58 ±4.82. Symptom score is predicted by disease duration (negatively) and hospital admission  (positively), activity score and impact score cannot be predicted by any of independent variables and total score is predicted by forced expiratory volume in the first second (negatively) and hospital admission  (positively).